Proceedings: second workshop on home sewage disposal in Colorado - Ward, Robert C., editor; Colorado State University. Environmental Resources Center, publisher (Colorado State University. Libraries, 1975)
The 2nd workshop on home sewage disposal in Colorado was held on September 17, 1975 at Colorado State University in Fort Collins, Colorado.
Second workshop on home sewage disposal in Colorado
Held September 17, 1975.
Keywords: Drainage, House -- Colorado -- Congresses; Septic tanks -- Colorado -- Congresses